Friendship and self-knowledge. On the role of friendship in Greek ethics (1985) (2021)
Translation of the text “Freundschaft und Selbsterkenntnis. Zur Rolle der Freundschaft in der griechischen Ethik”, a lecture given in Munich on July 12, 1983, originally published in Würzburger Jahrbücher für die Altertumswissenschaft (Beiheft 1, 1985, pp. 25-33) and republished with corrections in volume vi of Gesammelte Werke (1991, pp. 396-406). The present Castilian version is based on this last source.